Interleukin family in vascular calcification: molecular mechanisms and therapeutic perspectives - Zhao, Yikun; Li, Heng; Guo, Yuanyuan (Frontiers in Cardiovascular Medicine, 2025)
Vascular calcification (VC), characterized by pathological calcium deposition in arterial walls, is a major contributor to cardiovascular morbidity in chronic inflammatory diseases such as atherosclerosis, chronic kidney disease (CKD), and diabetes. Emerging evidence underscores the pivotal role of interleukin (IL) family cytokines in modulating VC through dual pro- and anti-calcific mechanisms. Pro-inflammatory IL members, including IL-1β, IL-6, IL-17A, and IL-29, drive osteogenic transdifferentiation of vascular smooth muscle cells (VSMCs) by activating pathways such as NF-κB, STAT3, NLRP3 inflammasomes, and Wnt/β-catenin. These pathways upregulate osteogenic markers (e.g., Runx2, BMP-2) and promote oxidative stress, matrix remodeling, and pyroptosis. Conversely, anti-inflammatory cytokines like IL-10 counteract calcification by suppressing inflammatory signaling, enhancing autophagy, and restoring mineral homeostasis. This review highlights the dynamic interplay between IL cytokines, metabolic dysregulation, and epigenetic modifications in VC pathogenesis. It advocates for multi-target approaches, such as combining TYK2/STAT3 inhibition with metabolic reprogramming, to disrupt pathological crosstalk. Future research must address spatiotemporal heterogeneity in IL signaling and optimize therapeutic specificity to translate mechanistic insights into clinical applications. Harnessing the IL family's dual roles offers transformative potential for mitigating VC while preserving immune integrity.